Enduring health effects of asbestos use in Belgian industries: a record-linked cohort study of cause-specific mortality (2001–2009) - Laura Van den Borre; Patrick Deboosere (BMJ Open)
Objective To investigate cause-specific mortality among asbestos workers and potentially exposed workers in Belgium and evaluate potential excess in mortality due to established and suspected asbestos-related diseases.Design This cohort study is based on an individual record linkage between the 1991 Belgian census and cause-specific mortality information for Flanders and Brussels (2001–2009).Setting Belgium (Flanders and Brussels region).Participants The study population consists of 1 397 699 male workers (18–65 years) with 72 074 deaths between 1 October 2001 and 31 December 2009. Using a classification of high-risk industries, mortality patterns between 2056 asbestos workers, 385 046 potentially exposed workers and the working population have been compared.Outcome measures Standardised mortality ratios (SMRs) and 95% CIs are calculated for manual and non-manual workers.Results Our findings show clear excess in asbestos-related mortality in the asbestos industry with SMRs for mesothelioma of 4071 (CI 2327 to 6611) among manual workers and of 4489 (CI 1458 to 10 476) among non-manual workers. Excess risks in asbestos-related mortality are also found in the chemical industry, the construction industry, the electrical generation and distribution industry, the basic metals manufacturing industry, the metal products manufacturing industry, the railroad industry, and the shipping industry. Oral cancer mortality is significantly higher for asbestos workers (SMR 383; CI 124 to 894), railroad workers (SMR 192; CI 112 to 308), shipping workers (SMR 172; CI 102 to 271) and construction workers (SMR 125; CI 100 to 153), indicating a possible association with occupational asbestos exposure. Workers in all four industries have elevated mortality rates for cancer of the mouth. Only construction workers experience significantly higher pharyngeal cancer mortality (SMR 151; CI 104 to 212).Conclusions The study identifies vulnerable groups of Belgian asbestos workers, demonstrating the current-day health repercussions of historical asbestos use. Results support the hypothesis of a possible association between the development of oral cancer and occupational asbestos exposure.